Electroacupuncture Inhibits NLRP3 Activation by Regulating CMPK2 After Spinal Cord Injury - Chen, Yi; Wu, Lei; Shi, Mengting; Zeng, Danyi; Hu, Rong; Wu, Xingying; Han, Shijun; He, Kelin; Xu, Haipeng; Shao, XiaoMei; Ma, Ruijie (Frontiers in Immunology, 2022)
We observed the expression of CMPK2 and the activation of NLRP3 inflammasome on SCI rats, the key role of electroacupuncture from the perspective of CMPK2 regulating the activation of NLRP3 inflammasome. We established SCI rat model on SD rats. The expression of NLRP3 and CMPK2 at different time points after spinal cord injury was observed in rats. The rats were randomly divided into sham, model, electroacupuncture, AAV CMPK2 and AAV NC group. EA was performed at jiaji points on both sides of section IX thoracic vertebrae and section XI thoracic vertebrae of SCI model rats, 20 minutes once a day, for 3 consecutive days. In the AAV CMPK2 and AAV NC groups, the virus was injected into the T9 spinal cord with a microneedle by a microscope using a stereotactic syringe. BBB score was used to evaluate the motor function of rats in each group. The histopathological changes of spinal cord tissues were detected by HE staining, and the expressions of NLRP3, CMPK2, ASC, Caspase-1, IL-18 and IL-1β were observed by western blotting, immunofluorescence and RT-PCR. Firstly, we found that the expressions of NLRP3 and CMPK2 in the spinal cord of the model group were significantly increased from day 1, the differences were statistically significant compared with the blank group (P < 0.05). The expression decreased gradually over time, and remained at a low level 14 days after injury. Secondly, we successfully constructed AAV CMPK2, and observed that the knockdown effect of the virus was more significant after 2 times dilution. Finally, it was found that BBB score of the EA group and AAV CMPK2 group was significantly increased, compared with the model group and AAV NC group (P < 0.05). The histomorphology of spinal cord in EA group and AAV CMPK2 group was changed. WB, IF and PCR showed that the expressions of CMPK2, NLRP3, ASC, Caspase-1, IL-18 and IL-1β were significantly decreased in the EA group and AAV CMPK2 group (P < 0.05). CMPK2 can regulate NLRP3 expression in rats with spinal cord injury. EA can down-regulate the expression of CMPK2 and inhibit the activation of NLRP3.